Gender and Justice in Afghanistan - World Bank (World Bank, Washington, DC, 2020)
The gender and justice study is to understand women's legal issues and justice seeking behaviors in four regions of Afghanistan. It focuses on four main themes, including: a) women's main legal issues; b) women's justice-seeking choices and rationale for those choices; c) the challenges women face when trying to access justice institutions; and d) women's satisfaction with the judicial process they experience in north (Kabul), west (Herat), central highlands (Bamyan), and east (Nangarhar, Logar). The study is underpinned by a conceptual framework that privileges understanding the dynamics of the demand for justice first, with a secondary focus on the supply side of justice. It has focused primarily on collecting data and information directly from actual or potential users of justice institutions, with efforts to maintain a gender balance among respondents. The knowledge and perspectives of justice service providers or other supply-side actors (like donors or program designers) have been used primarily to complement or be compared with data from the demand side.